Multiple testing in large-scale contingency tables: inferring patterns of pair-wise amino acid association in β-sheets. (10th May 2006) - Kim, Seoung Bum; Tsui, Kwok-Leung; Borodovsky, Mark
This study examines the feasibility of using multiple testing procedures for an inference of independence of categories in each cell in contingency tables. In the simulation study, we compare the performance of various multiple testing procedures in a contingency table setup and demonstrate the relationship among the proportion of true null hypothesis, type I error, power, and false discovery rate. Finally, we apply the proposed methodology to identify the patterns of pair-wise associations of amino acids involved in β-sheet bridges in proteins. We identify a number of amino acid pairs that exhibit either strong or weak association.